2015
DOI: 10.1371/journal.pone.0143848
|View full text |Cite
|
Sign up to set email alerts
|

Brain Swelling and Loss of Gray and White Matter Differentiation in Human Postmortem Cases by Computed Tomography

Abstract: The purpose of this study was to evaluate the brain by postmortem computed tomography (PMCT) versus antemortem computed tomography (AMCT) using brains from the same patients. We studied 36 nontraumatic subjects who underwent AMCT, PMCT, and pathological autopsy in our hospital between April 2009 and December 2013. PMCT was performed within 20 h after death, followed by pathological autopsy including the brain. Autopsy confirmed the absence of intracranial disorders that might be related to the cause of death o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Brain swelling [9,10] and the loss of GM-WM differentiation [8] are often observed on PMCT. However, brain swelling and other common PMCT findings also resemble the findings for HIE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain swelling [9,10] and the loss of GM-WM differentiation [8] are often observed on PMCT. However, brain swelling and other common PMCT findings also resemble the findings for HIE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that brain PMCT shows an increase in white matter (WM) attenuation, a decrease in gray matter (GM) attenuation, the loss of GM-WM differentiation [8,9], and diffuse brain swelling represented by a decrease in the size of the ventricles and sulci [9,10]. In most cases, these changes are nonspecific and not pathognomonic.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications of PMCT, it is important to differentiate disease-oriented pathological change from post-mortem change. However, systematic studies evaluating post-mortem change in PMCT are rarely focusing on longitudinal post-mortem observations[ 21 – 25 ], particularly for post-mortem brain alterations [ 20 , 26 ]. To address this issue, the current study included an assessment of post-mortem change in PMCT, which will be referred to as a “sequential scan project.” This sequential scan paradigm includes successive, periodical CT scans of the same post-mortem subject.…”
Section: Introductionmentioning
confidence: 99%
“…Using a sequential scan procedure, it is possible to observe the unfolding of post-mortem change inside the whole body, without a destructive inspection. Post-mortem brain alterations including CSF volume changes have been described [ 3 , 20 , 26 , 28 ], but there is still a need for clarification of the extent of these phenomena in comparison to antemortem brain edema as some authors denied brain swelling in the very early PMI [ 20 ]. The LCV volumes have recently been described as weak indicators of ante mortem cerebral edema [ 28 ] but their post mortem alteration had not been exactly deliminated in that retrospective study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation